2011
DOI: 10.1126/science.1200083
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Powerful Gamma-Ray Flares from the Crab Nebula

Abstract: The well-known Crab Nebula is at the center of the SN1054 supernova remnant. It consists of a rotationally powered pulsar interacting with a surrounding nebula through a relativistic particle wind. The emissions originating from the pulsar and nebula have been considered to be essentially stable. Here, we report the detection of strong gamma-ray (100 mega-electron volts to 10 giga-electron volts) flares observed by the AGILE satellite in September 2010 and October 2007. In both cases, the total gamma-ray flux … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
264
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(269 citation statements)
references
References 24 publications
4
264
1
Order By: Relevance
“…instabilities in the Anvil at the South-East jet base. Variability in this region was detected by optical and X-ray observations both during the September 2010 and April 2011 gamma-ray flares (Tavani et al 2011;. MHD simulations of the Crab South-East jet (Mignone et al 2013) revealed substantial jet deviation and magnetic dissipation.…”
Section: Multiwavelength Follow-up Of Crab Pwn Flaresmentioning
confidence: 99%
See 3 more Smart Citations
“…instabilities in the Anvil at the South-East jet base. Variability in this region was detected by optical and X-ray observations both during the September 2010 and April 2011 gamma-ray flares (Tavani et al 2011;. MHD simulations of the Crab South-East jet (Mignone et al 2013) revealed substantial jet deviation and magnetic dissipation.…”
Section: Multiwavelength Follow-up Of Crab Pwn Flaresmentioning
confidence: 99%
“…The prominent south-eastern (SE) jet (see Figure 1) also shows quite remarkable changes in its shape, based on Xray images (taken over 14-year baseline), which could be explained by either precession of the curved jet or by the motion of kinks along the jet (Weisskopf 2012;Deshpande and Radhakrishnan 2007). Finally, the unexpected detection of γ-ray flares by Fermi LAT and AGILE (Buehler et al 2012;Abdo et al 2011b;Tavani et al 2011) suggests a significant energy release rate (which can reach 4 × 10 36 erg s −1 ; Buehler et al 2012) on timescales of hours ); however, it was not possible so far to pinpoint the location of the flaring region because of the lack of a "smoking gun" at lower frequencies. Consequently, the lack of information about the site of the flare in the PWN has led to a variety of models being suggested (see § 3).…”
Section: Multiwavelength Properties Of the Crabmentioning
confidence: 99%
See 2 more Smart Citations
“…The surprising discovery of short-lived, bright gamma-ray flares from the Crab Nebula (Tavani et al 2011;Abdo et al 2011) could be the direct evidence of magnetic reconnection in the Nebula Clausen-Brown and Lyutikov 2012;Cerutti et al 2014a). Using 2D and 3D PIC simulations, Cerutti et al (2013Cerutti et al ( , 2014b showed that most of the features of the flares can be explained with relativistic reconnection (timescale, energetics, particle and photon spectra).…”
Section: Pulsars and Pulsar Wind Nebulaementioning
confidence: 99%